Prevalence of mental health conditions amongst people living with human immunodeficiency virus in one of the most deprived localities in England. (June 2020) - Gill, A; Ranasinghe, AWIP; Sumathipala, A; Fernando, KA
: Mental health conditions (MHCs) are often unrecognised which can result in detrimental physical health outcomes and poor quality of life. This can be compounded by the impact of deprivation. People living with human immunodeficiency virus (PLWH) are more likely to be affected by MHCs which if untreated, may result in both clinical and psychosocial adversities. To ascertain the prevalence of and factors associated with MHCs in the human immunodeficiency virus cohort of Stoke-on-Trent, which is the 13th most deprived locality in England, we conducted a cross-sectional service evaluation using electronic records of 302 PLWH attending the service between October 2018 and January 2019. The prevalence of MHCs amongst PLWH was 33.4% (101/302). Depression was the most prevalent MHC affecting 17.2% (52/302). Those of white ethnicity were at higher risk (odds ratio [OR] = 3.14; p < 0.01) of MHCs compared to black Asian and minority ethnic groups. Women were at higher risk of having an MHC (OR = 3.15; p < 0.01), and recreational drug use was also a significant factor (OR = 16.18; p = 0.01) associated with MHCs. There is sub-optimal access and heterogeneity in the modes of referral to mental health support services. Commissioning constraints will further detrimentally affect our ability to provide support in an already deprived area, thus widening health inequalities affecting the most vulnerable.